1967
DOI: 10.1103/physrevlett.18.839
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Specific Heat of Gold-Silver Alloys

Abstract: PHYSICAL REVIEW LETTERS 15 MAY 1967 in Ref. 5, it was necessary, to make the computation of A (2) tt(0) tractable, to employ a static limit for the full dynamic potential. 9 Also a spherical average over the directions of p was introduced. It should be stressed, however, that it was not possible to show that the analytic expressions .themselves ensure positive definiteness. In fact, they almost certainly do not. Nevertheless, the remaining descrepancy for a = 0.25 is small as compared to the RPA result, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
1983
1983

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…given by Martin (1968c), for purezinc Martin,2 where I i s the nuclear spin, Q is the electric quadand for pure indium by O'Neal and Phillips ,upole moment (=0.58 10-z4 Cm2 for gold), (1965). Linear interpolation between these results , is the charge on an electron, eq the electric field would give, for the goldlo atomic % zinc alloy, gradient, R the gas constant, and k is BOltzmann's estimated (Stern 1966) to be about 0.2 electrons The variation on alloying of the per atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…given by Martin (1968c), for purezinc Martin,2 where I i s the nuclear spin, Q is the electric quadand for pure indium by O'Neal and Phillips ,upole moment (=0.58 10-z4 Cm2 for gold), (1965). Linear interpolation between these results , is the charge on an electron, eq the electric field would give, for the goldlo atomic % zinc alloy, gradient, R the gas constant, and k is BOltzmann's estimated (Stern 1966) to be about 0.2 electrons The variation on alloying of the per atom.…”
Section: Resultsmentioning
confidence: 99%
“…uated, sealed, internally carbon-coated quartz A small nuclear specific-heat term was noticed (Martin 1967a(Martin , 1968a in nonmagnetic facecentered-cubic gold-silver alloys. It was suggested that, although the lattice was cubic, electric field gradients would exist in these disordered alloys and remove the degeneracy associated with the nuclear electric quadrupole moment of gold.…”
Section: Introductionmentioning
confidence: 99%